Murray F. Tuley, ed., Laws and Ordinances Governing the City of Chicago (Chicago, IL: The Bulletin Printing Co., 1873), 11–13. Chapter 8—Concealed Weapons, §§ 1-9. Enacted August 17, 1871 - (:unkn) unknown (General Publisher, 1871)
Prohibited anyone from carrying or wearing under their clothes, or concealed about their person any pistol, colt, slung shot, cross knuckles, knuckles of lead, brass, or other metal, or Bowie-knife, dirk, dagger, or any other dangerous or deadly weapon. Violators shall have weapons seized, and shall be fined not exceeding one hundred dollars, or imprisoned not exceeding six months, or both fine and imprisonment.
--
Keywords: CARRY - CONCEALED